Cytokine and Complement Response in the Glaucomatous βB1-CTGF Mouse Model - Reinehr, Sabrina; Doerner, Johanna D.; Mueller-Buehl, Ana M.; Koch, Dennis; Fuchshofer, Rudolf; Dick, H. Burkhard; Joachim, Stephanie C. (Frontiers in Cellular Neuroscience, 2021)
Glaucoma is a complex neurodegenerative disease leading to a loss of retinal ganglion cells (RGCs) and optic nerve axons. An activation of the complement system seems to contribute to cell loss in this disease. Hence, we investigated a possible initiation of the complement system and the cytokine response in the βB1-CTGF glaucoma model. In these mice, intraocular pressure is elevated, which is the main glaucoma risk factor in patients, and RGC loss occurs at 15 weeks of age. Therefore, quantitative real-time PCR and immunohistological experiments were performed in 5-, 10-, and 15-week-old βB1-CTGF animals and their corresponding wildtypes (WT) to analyze the expression of several complement system factors. We could show that mRNA levels of the terminal complement pathway components C3 and C5 (Hc) were upregulated at 10 weeks. In accordance, more C3+ and membrane attack complex+ cells were observed in transgenic retinae. Further, the C5a receptor anaphylatoxin receptor (C5ar) and the complement component C5a receptor 1 (C5ar1; CD88) mRNA levels were upregulated in 10- and 15-week-old βB1-CTGF mice. Interestingly, all three activation routes of the complement system were elevated in βB1-CTGF mice at some age. Especially C1q, as a marker of the classical pathway, was significantly increased at all investigated ages. Furthermore, mRNA expression levels of interferon-γ (Infg) were upregulated at 5 weeks, while Cxcl1 and Cxcl2 mRNA levels were upregulated at 10 and 15 weeks. The mRNA levels of the chemokines Cxcl10 were increased at all ages in βB1-CTGF mice. These results lead to the assumption that in these transgenic mice, a complement activation mainly through the classical pathway as well as a cytokine response plays a major role in cell death.